WHAT IS A [[CONTEMPORARY]] INDEX? - Monteiro, Silvana Drumond [UNESP]; Carneiro Giraldes, Maria Julia (Univ Federal Campina Grande, 2019)
Indexes are paratexts, that is, supplementary texts and of an epistemic nature different from the texts they index, but strictly related to them. They are important tools for organizing and retrieving information. Throughout history they are associated with the documentary conception, that is, with books. However, its etymology and its pragmatics refer to the previous semiotic concept of indicating, pointing or giving direction. From this retrospective view the research question is: what is a contemporary index? It is especially a search index, generated by a search engine through a request or search. In view of the objective of knowing the structure of a contemporary index, based on the Google search, that is generated in a Search Engine Results Page (SERP), we sought the analysis of its anatomy, that is, the constituent elements of its structure, according to Morville and Callender (2010), through a documentary analysis as a method, and the identification, from documentary research, of the basic structure of an index in Wheatley's classic essay (1879) entitled What is an index?. After the comparison of these indices, it was observed that their basic structure changed, given the performative nature of the digital substrate used as their medium, presenting more elements, at the same time as reinforcing their semiotic indexical linking aspect. They are, today, our informational compasses.
Keywords: Index; SERP; Google; Search Engine